Moral development and reality : beyond the theories of Kohlberg and Hoffman - Gibbs, John C. (SAGE, 2003)
Moral Development and Reality: Beyond the Theories of Kohlberg and Hoffman explores the nature of moral development, social behavior, and human interconnectedness. By comparing, contrasting, and going beyond the works of pre-eminent theorists Lawrence Kohlberg and Martin Hoffman, author John C. Gibbs addresses fundamental questions: What is morality? Can we speak validly of moral development? Is the moral motivation of behavior primarily a matter of justice or of empathy? Does moral development, including moments of moral inspiration, reflect a deeper reality? Moral Development and Reality elucidates the full range of moral development from superficial perception to a deeper understanding and feeling through social perspective-taking. Providing case studies and chapter questions, Gibbs creates a unique framework for understanding Kohlberg's and Hoffman's influential contributions.- Resumé vydavatel
Keywords: Kohlberg, Lawrence, -- 1927-1987; Hoffman, Martin L., -- 1924-; morální vývoj; morálka; sociální chování; moral development; morality; social behavior; elektronické knihy; monografie; electronic books; monographs